Impact of Mast Cells on the Skin. (October 2013) - Kritas, S.K.; Saggini, A.; Varvara, G.; Murmura, G.; Caraffa, A.; Antinolfi, P.; Toniato, E.; Pantalone, A.; Neri, G.; Frydas, S.; Rosati, M.; Tei, M.; et al.
When through the skin a foreign antigen enters it provokes an immune response and inflammatory reaction. Mast cells are located around small vessels that are involved in vasaldilation. They mature under the influence of local tissue to various cytokines. Human skin mast cells play an essential role in diverse physiological and pathological processes and mediate immediate hypersensitive reaction and allergic diseases. Injection of anti-IgE in the skin or other agents that directly activate mast cells may cause the decrease in vascular tone, leakage of plasma and may lead to a fall in blood pressure with fatal anaphylactic shock. Skin mast cells are also implicated as effector cells in response to multiple parasites such as Leishmania which is primarily characterized by its tissue cutaneous tropism. Activated macrophages by IFNγ, cytotoxic T cells, activated mast cells and several cytokines are involved in the elimination of the parasites and immunoprotection. IL-33 is one of the latest cytokines involved in IgE-induced anaphylaxis and in the pathogenesis of allergic skin disorders. IL-33 has been shown in epidermis of patients with psoriasis and its skin expression causes atopic dermatitis and it is crucial for the development of this disease. Here we review the impact of mast cells on the skin.